Inhibition of Carrageenan-Induced Cutaneous Inflammation by PPAR Agonists Is Dependent on Hepatocyte-Specific Retinoid X Receptor Alpha - Yu-Jui Yvonne Wan; Mostafa Z. Badr (PPAR Research)
It has been proposed that PPAR-dependent, accelerated catabolism of proinflammatory mediators may contribute to the fast resolution of inflammation. Because retinoid X receptors are obligate heterodimer partners of PPARs, we investigated the impact of deleting hepatocyte-specific RXRα on the antiedema effect of PPAR agonists. In wild-type mice (WT), pretreatment with the PPARα agonist perfluorooctanoic acid diminished carrageenan-induced paw edema by 66±10%. This effect was essentially absent (13±8%) in hepatocyte-specific RXRα-deficient mice. Similarly, pretreatment of WT mice with the PPARδ agonist L-783483 or the PPARγ agonist L-805645 caused 54±1% and 38±8% reduction in carrageenan-induced paw edema, respectively. These effects were also significantly diminished or absent in hepatocyte-specific RXRα-deficient mice. In contrast, aspirin reduced carrageenan-induced paw edema equally in WT and hepatocyte-specific RXRα-deficient mice. The identification of RXRα as an important factor involved in the antiedema effect produced by agonists of the three PPAR subtypes is a significant achievement towards the goal of designing novel, effective anti-inflammatory drugs.